GAMBARAN PENGETAHUAN, SIKAP DAN PERILAKU IBU TENTANG PEMBERIAN IMUNISASI DASAR LENGKAP PADA BAYI DI WILAYAH KERJA PUSKESMAS SELALONG KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - ., Abang Anton (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Immunization activities is one of the priority activities of theMinistry of Health as one of the government's commitment to achieve theMillennium Development Goals (MDGs), especially, for reduce mortality ofchildren. Factors the play role importance influencing of the immunizationstatus is knowledge, attitude and behavior of the mother's. Data from theDistrict Health Profile Sekadau in 2011, coverage the lowest immunizationis Selalong health center. Method: This study used a descriptive studywith cross sectional approach. The sampling technique used nonprobability with the consecutive sampling methode. Data collection wasconducted by administering questionnaires to 32 respondents. The datawas processed to use SPSS 19. Results: 16 respondents (50%) is poorknowledge, 15 respondents (46,9%) is moderate stance, 17 respondents(53,1%) is bad behavior. The general age is 30 respondents to age 20-35years (93,8%), the highest completed education is junior high school whichis 14 respondents (43,8%), the job is farmers which is 24 respondents(75%), husband's income under the Minimum Salary Employee which is18 respondents (56,3%), the number of children is two sons which is 17respondents (53,1%), the largest information resources is from the healthcare worker (78,2%), the immunization services is from health center /neighborhood health center (90,7%). Conclusion: The Knowledge is bad.the attitud is moderate, the behavior is bad regard with age, education,occupation, husband's income, number of children, information resourcesand immunization services. Keywords : Knowledge, Attitude, Behaviour, Immunization1) Medical School, Faculty of Medicine, Tanjungpura University, Pontianak, West Borneo2) Department of Public Health Care, Faculty of Medicine, Tanjungpura University, Pontianak, West Borneo3) Department of Physiology, Faculty of Medicine, Tanjungpura University, Pontianak, West Borneo